The effect of the 5ws&1h strategy on the achievement of fifth-grade primary school students in Arabic grammar (Journal of the College of Basic Education, 2023)
This research aims to identify (the impact of the 5WS & 1H strategy on the achievement of the fifth grade students in the subject of the grammar of the Arabic language), the researcher followed the experimental curriculum, and relied on an experimental design with partial control, which is the design of the experimental group and the control group in the post -test, the researcher chose his formed sample sample From (63) pupils, experimental (31) pupils, the officer (32) students at the Junaid Primary School of the General Directorate of Karkh First Education in Baghdad Governorate, and the statistical analysis sample consisted of (153) students. The researcher has rewarded among the students of the two groups of research in a number of variables, including: the timeline of the students calculated in the months, the grades of the Arabic language for the previous year and the academic achievement of parents, the previous knowledge test, the test of intelligence, then tried to control a number of exotic variables that previous literature and studies indicated that they may It affects this type of experimental designs. The researcher prepared an achievement test as a tool for research consisting of (30) paragraphs distributed between two questions, the first consists of (20) paragraphs of the multiple choice type, and the second consists of (10) paragraphs of the type of correct and error, applied to the search, experimental and control groups at the end Experience, using the two independent samples test, resulted in the search for the following result: The presence of a statistically significant difference at the level of significance (0,05), as the students of the experimental group who studied the subject of Arabic grammar exceeded the 5WS & 1H strategy on the students of the control group who studied the subject of Arabic grammar itself in the traditional way.